School Students’ Perception on Risky Behavior and Their Utilization of Health Care Services - Muhammad Kamil Che Hasan; Noor Faizah Tutasting@Rawi; Mohd Said Nurumal; Siti Hazariah Abdul Hamid (Jurnal Keperawatan Indonesia, 2021)
The Malaysia Ministry of Health reported adolescents’ low utilization of healthcare services, although they need this service as a consequence of their involvement in risky behavior. This cross-sectional study aimed to determine adolescents' perception on risk taking behavior and their utilization of health care services. A modified self-administered questionnaire was used to collect data from 250 secondary school students aged 13 and 14 years in one of the selected schools in Malacca, Malaysia. Data were analyzed using SPSS 20. Fast food consumption, loitering after school, physical fighting, smoking, and non-use of helmets were the most reported risky behaviors among adolescents in Malaysia. More than half of the adolescents who knew about health care services had a positive perception on their utilization of such services. Thus, the promotion of adolescents’ health services helps increase their use of these services and consequently achieve a healthy lifestyle. Abstrak Persepsi Siswa Sekolah terhadap Perilaku Risiko dan Pemanfaatan Layanan Perawatan Kesehatan. Kementerian Kesehatan Malaysia melaporkan rendahnya pemanfaatan layanan kesehatan oleh remaja, meskipun mereka membutuhkan layanan ini sebagai konsekuensi dari keterlibatan mereka dalam perilaku berisiko. Studi cross-sectional ini bertujuan untuk mengetahui persepsi remaja tentang perilaku pengambilan risiko dan pemanfaatannya terhadap layanan perawatan kesehatan. Kuesioner mandiri yang dimodifikasi digunakan untuk mengumpulkan data dari 250 siswa sekolah menengah berusia 13 dan 14 tahun di salah satu sekolah yang dipilih di Malaka, Malaysia. Data dianalisis menggunakan SPSS 20. Konsumsi makanan cepat saji, berkeliaran sepulang sekolah, perkelahian fisik, merokok, dan tidak menggunakan helm adalah perilaku berisiko yang paling banyak dilaporkan di kalangan remaja di Malaysia. Lebih dari setengah remaja yang tahu tentang layanan perawatan kesehatan memiliki persepsi positif tentang pemanfaatan layanan tersebut. Dengan demikian, promosi layanan kesehatan remaja membantu meningkatkan penggunaan layanan ini dan akibatnya mencapai gaya hidup sehat. Kata Kunci: layanan perawatan kesehatan remaja, perilaku berisiko, sekolah